Pembelajaran Mata Kuliah Japanese Vocabulary 2 dengan Metode Gambar - Diah Soelistyowati (Japanese Research on Linguistics, Literature, and Culture, 2019)
Japanese Vocabulary 2 courses in Japanese Literature Dian Nuswantoro University are courses that teach Japanese vocabulary which is learned in Kanji letters. This Japanese Vocabulary course is given in semester 3 and semester 4 which is a follow-up course from Japanese Character. However, this study,Â  the author will discuss Japanese Vocabulary 2 learning strategies by using picture slides, drill repetition of words, and Kanji letter vocabulary exercises in Japanese sentences contained in the Goi Nihongo maatome sou N3 textbook and Pea de Oboeru Iroirona Kotoba. The use of this teaching strategy can improve mastery of Japanese Kanji for students to be easy to learn so that learning targets set by Japanese Vocabulary 2 teaching goals can be achieved.